2016
DOI: 10.1155/2016/7867545
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Metastasis of a GIST: A Case Report and Review of the Literature

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common malignant mesenchymal tumors of the gastrointestinal tract. The most common sites of metastasis are the liver and the peritoneum, whereas metastasis to soft tissue is rare. The authors present the case of a 78-year-old male with a soft tissue metastasis of a GIST and the current literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Metastases to lymph nodes and extra-abdominal structures are uncommon, occurring in less than 10% of cases [18] . Skeletal muscle metastasis from a primary GIST is exceptionally rare, and to our knowledge, only 6 cases have been reported in the literature [8–13] . Pasku et al [8] reported a case of bilateral gluteal and lung metastases in a 56-year-old woman with a GIST of the pelvis, which was initially misdiagnosed as a uterine leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Metastases to lymph nodes and extra-abdominal structures are uncommon, occurring in less than 10% of cases [18] . Skeletal muscle metastasis from a primary GIST is exceptionally rare, and to our knowledge, only 6 cases have been reported in the literature [8–13] . Pasku et al [8] reported a case of bilateral gluteal and lung metastases in a 56-year-old woman with a GIST of the pelvis, which was initially misdiagnosed as a uterine leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the patient's unstable state of health, the lesion was not excised, and she received TKI therapy. Finally, Savvidou et al [ 13 ] reported the case of a 78-year-old man with medial right upper thigh metastases from an anal GIST. The patient subsequently underwent wide excision of the lesion, which confirmed the diagnosis of skeletal muscle metastases secondary to GIST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when intracranial GIST metastasis occurs, it usually affects the nervous system, resulting in dizziness, headache, memory impairment, loss of sensation and inability to move a single limb, the inability to maintain body balance and abnormal gait and posture, along with a series of neurological crements (27,32,35,40,51,61,70,87,87,92,93). In cases of bone metastasis, pain manifests in the affected bone area (29,37,48,52,53,63,69,75,80,94,95), in cases of skeletal muscle involvement, a mass can be palpated in the affected area (34,49,71,72,79), and when metastasis occurs deep in the bone marrow, anemia may be present (96). Furthermore, when GIST metastasizes to the lungs, signs and symptoms that may be observed include dyspnea, blood in the sputum, coughing and shortness of breath (18,85,88,97).…”
Section: Diagnosis Of Rare Site Metastasis Of Gistmentioning
confidence: 99%